2007
DOI: 10.1016/j.gie.2007.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of obscure GI bleeding at double balloon endoscopy

Abstract: DBE was relatively safe and useful for diagnosis and treatment of OGIB. A spectrum of small-bowel diseases presenting with OGIB in Japan may be distinct from that in the Western world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
131
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(139 citation statements)
references
References 16 publications
4
131
1
2
Order By: Relevance
“…Balloon-assisted enteroscopy is considered the second-line examination for patients with OGIB and positive findings in CE requiring further exploration or therapeutic intervention (10,27). However, the reported rates of total small bowel intubation vary widely (ranging from 0 to 86%), hampered by the presence of intestinal adhesions of previous surgery, obesity or with operators with less experience (19,20,23,25,(28)(29)(30). Nevertheless, when balloon enteroscopy approach is directed by CE findings, one-side procedure was sufficient to achieve the lesion in almost 90% of examinations (31).…”
Section: Discussionmentioning
confidence: 99%
“…Balloon-assisted enteroscopy is considered the second-line examination for patients with OGIB and positive findings in CE requiring further exploration or therapeutic intervention (10,27). However, the reported rates of total small bowel intubation vary widely (ranging from 0 to 86%), hampered by the presence of intestinal adhesions of previous surgery, obesity or with operators with less experience (19,20,23,25,(28)(29)(30). Nevertheless, when balloon enteroscopy approach is directed by CE findings, one-side procedure was sufficient to achieve the lesion in almost 90% of examinations (31).…”
Section: Discussionmentioning
confidence: 99%
“…Some [18,20] reported angiodysplasia as a main cause of OGIB, while others [19,21] report ulcers to be the main etiology. However, when considered large studies that include more than 100 patients, one study from India [21] and two double-balloon enteroscopy studies from Japan [22,23] , all showed that small bowel ulcers were the most common cause of OGIB (41%-53%), more common than angiodysplasia (23%-24%). These yielding rates are much closer to the results of our study (44% and 27% for ulcers and angiodysplasia, respectively).…”
Section: Characteristics Of Patients According To the Etiologymentioning
confidence: 99%
“…mucosal biopsy, argon plasma coagulation, snare polypectomy, injection therapy, tattooing, foreign body extraction and balloon dilatation. DBE plays an important role in the diagnosis and treatment of obscure gastrointestinal bleeding [3][4][5][6] , Crohn's disease [7][8][9][10] , celiac disease [11,12] , polyposis syndromes [13] and small bowel tumors. In the series published to date, complications solely related to the diagnostic procedure are rare [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%